THE USE OF ANIMATED SHORT FILM MEDIA SPEAKING CLASS AT AN INDONESIAN JUNIOR HIGH SCHOOL: CHALLENGES AND STUDENT'S RESPONSES - Maratusolekhah, Annisa; Hikmat, Mauly Halwat (TELL - US JOURNAL, 2023)
This study aims to describe the use of animated short films, the challenges faced by the teacher and the students’ response towards its implementation in Speaking class. This research employed descriptive qualitative design and the data were taken through interviews and observations. The participants of this study were 14 students from grade 9 and 1 teacher who were interviewed and observed. The result of this study showed: 1) The procedures of applying media, there are: showing playing the short film media, checking student’s understanding, repeating material explanation, giving assignments related to the media and checking student’s work and conducting evaluations related to the showing of the film. 2) teacher’s challenges in preparing animated short films, there are: getting relevant animated short films, finding interesting and easy understanding animation and determining the right duration, then teacher’s challenges in applying media are: student’s lack of enthusiasm for the material, teacher’s difficulties in time management and infrastructure problems. 3) Students perceive that the media used by the teacher gave positive responses to speaking skills such as increasing pronunciation, making learning enjoyable, stimulating English speaking skills and facilitating understanding of the material.